Energy, exergy, advanced exergy and economic analyses of hybrid polymer electrolyte membrane (PEM) fuel cell and photovoltaic cells to produce hydrogen and electricity - Shaygan, M.; Ehyaei, M. A.; Ahmadi, A.; Assad, M. El Haj; Silveira, José Luz [UNESP] (Elsevier, 2019)
Hydrogen, as a clean fuel, can provide all the requirements and characteristics of a clean and reliable energy carrier in the long term as a suitable alternative to fossil fuels. In this paper, a power generation system using hydrogen storage has been investigated. For this purpose, 64 photovoltaic modules with area of 2.16 m2 for each module and 329 PW and 5.5 kW PEM fuel cell and electrolyzer were used in this hybrid system. The day product of hydrogen day has been calculated as 158 kg. The system has been subjected to exergy analysis and, hence the efficiency and destruction of exergy components have been calculated. The annual average electrical production by photovoltaic system is 4850 W. The average annual exergy efficiency of each component including compressor, electrolyzer, fuel cell, and photovoltaic cell has been calculated as 75.9%, 11.2%, 32.8%, and 10.8%, respectively. The energy and exergy efficiencies of the system have been calculated for different days and its average annual values have been obtained 20.4% and 21.8%, respectively. Cost of electricity is 0.127 $/kWh, which is compatible with solar thermal and wind turbine offshore electricity costs. Finally, according to the advanced exergy analysis in all equipment's except the photovoltaic cell, the highest exergy destruction has been related to exogenous unavoidable.
Keywords: Advances; Economic; Electrolysis; Exergy; Fuel cell; Photovoltaic cells